Gambaran Karakteristik Kejadian Intrauterine Fetal Death ( IUFD) di Rumah Sakit Umum Daerah (RSUD) Berkah Pandeglang Tahun 2021 - Fida Asfia (Universitas Banten Jaya, 2023)
IUFD is one event that contributes to perinatal mortality. IUFD has a percentage of 29.5% as a cause of death in the perinatal group. Indonesia is in the 10 countries with the highest number of maternal and newborn deaths in the world, there are 2 mothers and 6 neonatal or newborn babies die every day in Indonesia. Meanwhile, the perinatal mortality rate in Indonesia is 21 deaths per 1000 pregnancies (Juwita et al., 2021). This research was conducted at Berkah Pandeglang Hospital, data collection was carried out in April 2022 with research subjects being pregnant women with IUFD in 2021. The sampling technique was total sampling with a total sample of 43 respondents. Data analysis technique used univariate analysis technique with cross sectional descriptive design. The results of the study found that the majority of respondents experienced Advanced IUFD events (gestational age> 24 weeks), namely as many as 62.8%, with the characteristics of respondents having a non-risk age category (20-35 years) namely as many as 58.1%, multipara parity, namely as many as 60.5% and Mass Index Body (BMI) Normal is as much as 65.1%.